Structural basis of DNA Ligase IV-Artemis interaction in Non-Homologous End Joining (NHEJ) - De Ioannes, Pablo (2012)
DNA ligase IV (LigIV) and Artemis are central components of the Non-Homologous End Joining (NHEJ) machinery that is required for V(D)J recombination and the maintenance of genomic integrity in mammalian cells. We report here crystal structures of the LigIV DNA binding domain (DBD) in both its apo form and in complex with a peptide derived from the Artemis C-terminal region. We show that LigIV interacts with Artemis through an extended hydrophobic surface. In particular, we find that helix α2 in LigIV DBD is longer than in other mammalian ligases and presents residues which specifically interact with the Artemis peptide that adopts a beta-helix conformation on binding. Mutations of key residues on the LigIV DBD hydrophobic surface abolish the interaction. Together, our results provide structural insights into the specificity of LigIV-Artemis interaction and how the enzymatic activities of the two proteins may be coordinated during NHEJ.